2014
DOI: 10.1371/journal.pone.0107123
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Network of Secondary Metabolism in Brassica rapa: Insight into the Glucosinolate Pathway

Abstract: Brassica rapa studies towards metabolic variation have largely been focused on the profiling of the diversity of metabolic compounds in specific crop types or regional varieties, but none aimed to identify genes with regulatory function in metabolite composition. Here we followed a genetical genomics approach to identify regulatory genes for six biosynthetic pathways of health-related phytochemicals, i.e carotenoids, tocopherols, folates, glucosinolates, flavonoids and phenylpropanoids. Leaves from six weeks-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The GSL metabolic pathway has been extensively investigated in Arabidopsis and has been well studied in B. rapa , broccoli, radish, etc. by genome wide homologous analysis (Wittstock and Halkier, 2002 ; Zang et al, 2009 ; Wang et al, 2011 ; Liu et al, 2014 ; Pino Del Carpio et al, 2014 ; Wiesner et al, 2014 ; Mitsui et al, 2015 ). In S. alba , many GSLs have been identified (Agerbirk et al, 2008 ; Popova and Morra, 2014 ; Vastenhout et al, 2014 ), and many studies on the functions of GSLs have been reported (Abdull Razis et al, 2012 ; Peng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The GSL metabolic pathway has been extensively investigated in Arabidopsis and has been well studied in B. rapa , broccoli, radish, etc. by genome wide homologous analysis (Wittstock and Halkier, 2002 ; Zang et al, 2009 ; Wang et al, 2011 ; Liu et al, 2014 ; Pino Del Carpio et al, 2014 ; Wiesner et al, 2014 ; Mitsui et al, 2015 ). In S. alba , many GSLs have been identified (Agerbirk et al, 2008 ; Popova and Morra, 2014 ; Vastenhout et al, 2014 ), and many studies on the functions of GSLs have been reported (Abdull Razis et al, 2012 ; Peng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cabbage ( Brassica oleracea L.) plants represent one of the major vegetable crops grown worldwide. Most crops of B. oleracea and its sister species Brassica rapa produce a range of phytochemicals with diverse functions for plant defense such as polyphenolic compounds, carotenoids, and glucosinolates [ 1 , 2 ]. The draft genome sequences of B. oleracea (with the CC genome) and B. rapa (with the AA genome) were recently published [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this approach not only detects the expression of a specific gene and the genotype at that gene's locus, but it also reveals clustered trans -eQTLs that are simultaneously regulated by a large fraction of the transcriptome (Brem et al, 2002; Schadt et al, 2003; Morley et al, 2004). This approach has been successfully used in crop plants to detect transcript-level variation and downstream phenotypic trait variation (Jordan et al, 2007; Shi et al, 2007; West et al, 2007; Potokina et al, 2008; Xiao et al, 2013, 2014; Del Carpio et al, 2014; Basnet et al, 2015, 2016). Although eQTLs have successfully been cloned in plants (Werner et al, 2005; Zhang et al, 2006), global eQTL analysis in a large mapping population of plants has not hitherto been performed.…”
Section: Introductionmentioning
confidence: 99%